A Novel b-Orcinol Depsidone of Lichen Lobaria pulmonaria - Pejin1, B.; Iodice2, C.; Stanimirovic3, B.; Vajs4, V.; Tesevic5, V. (Asian Journal of Chemistry, 2014)
In continuation of our phytochemical survey of Lobaria pulmonaria has led to the identification of deoxystictic acid in this foliose lichen species for the first time. The isolated b-orcinol depsidone showed moderate anti-hydroxyl radical activity using fluorescence spectroscopy at in vitro conditions.